KODE ETIK ADVOKAT SEBAGAI PEDOMAN DALAM PENEGAKAN HUKUM - Fransiska Novita Eleanora (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2014)
Advocate is a person whose profession gives legal services that include providing legal advice, legal assistance, exercise the power, represent, assist, defend, and perform other legal acts for the benefit of clients both inside and outside the court by getting the honorarium or fee received for legal services based on agreements with clients or provide legal services free of charge to clients who can not afford and have a requirement under the provisions of law. Advocates as a law enforcement position that has the equivalent of other law enforcement agencies in enforcing the law and justice. Any legal proceedings, whether criminal, civil, administrative, and even statecraft, always involves professional advocates whose position is equivalent toother law enforcement agencies. Advocate is an integral part of the judicial system itself, have a moral obligation to help ensure that the principles of justice (administration of justice) that both must be met in the legal system to seek fair trial and right (fair trial).